2016
DOI: 10.21566/tarbitderg.281885
|View full text |Cite
|
Sign up to set email alerts
|

Farklı Cins Hayvan ile Otlatılan Meraların Sağlık ve Ekolojik Alan Sınıflaması

Abstract: Rangelands can renew itself or go backwards depending on the ecological factors. Rangelands exhibit positive, negative or neutral depending on using properties. The objective of this study was to determine rangeland health and ecological site distribution of grazed rangeland with cattle, sheep and mixed stocking in the Kargapazari Mountain Erzurum province. In the investigated rangelands, vegetation, soil and hydrology properties differed significantly. As a result of this study, it is possible to state that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 13 publications
(13 reference statements)
2
25
1
Order By: Relevance
“…Indeed, these results indicated that changes in the rangeland structure and dynamics due to the GP × GAS interactions may result in changes in rangeland supply and carrying capacity over the longer term. In terms of BC, the results support idea that the presence of sheep and goats in grazing systems could, also, have highly beneficial consequence or that rangelands grazed by mixtures of goats, sheep and cattle can have more invader herbaceous species than rangelands grazed by cattle alone (Benavides et al, 2009;Utsumi et al, 2010;Erkovan et al, 2016). A dramatically decrease in invader species such as Dryopteris filix-mas L. and Schott and Galega officinalis L. in the MSG rangelands compared to those of the SSG rangelands (data not shown) support ideas that the utilization of heterogeneous plant resources can be enhanced due to the complementary grazing of goats (Benavides et al, 2009).…”
Section: Experiments Isupporting
confidence: 68%
See 4 more Smart Citations
“…Indeed, these results indicated that changes in the rangeland structure and dynamics due to the GP × GAS interactions may result in changes in rangeland supply and carrying capacity over the longer term. In terms of BC, the results support idea that the presence of sheep and goats in grazing systems could, also, have highly beneficial consequence or that rangelands grazed by mixtures of goats, sheep and cattle can have more invader herbaceous species than rangelands grazed by cattle alone (Benavides et al, 2009;Utsumi et al, 2010;Erkovan et al, 2016). A dramatically decrease in invader species such as Dryopteris filix-mas L. and Schott and Galega officinalis L. in the MSG rangelands compared to those of the SSG rangelands (data not shown) support ideas that the utilization of heterogeneous plant resources can be enhanced due to the complementary grazing of goats (Benavides et al, 2009).…”
Section: Experiments Isupporting
confidence: 68%
“…A dramatically decrease in invader species such as Dryopteris filix-mas L. and Schott and Galega officinalis L. in the MSG rangelands compared to those of the SSG rangelands (data not shown) support ideas that the utilization of heterogeneous plant resources can be enhanced due to the complementary grazing of goats (Benavides et al, 2009). Thus, the presence of goats in MSG may be a more proficient way for productive as well as ecological goals (Benavides et al, 2009) or increase the sustainability of the pastoral system by maintaining more desirable species in rangelands compared to SSG system with cattle or sheep alone Erkovan et al, 2016).…”
Section: Experiments Imentioning
confidence: 99%
See 3 more Smart Citations